Predictors of occupational exposure to HIV infection among healthcare workers in southern Ethiopia - Beyene, Tadewos; Tadesse, Sebsibe (International Journal of Infection Control, 2014)
Abstract Occupational risk of HIV transmission is a major concern for healthcare workers worldwide. However, there is a paucity of studies clarifying the situation in most of Subsaharan African countries like Ethiopia. The objectives of this study were to determine the prevalence of occupational exposure to HIV infection, and to identify the associated factors among healthcare workers at government health institutions in Hawassa Town, southern Ethiopia. An institution-based cross-sectional study was conducted at two hospitals and six health centers run by Government in Hawassa Town, southern Ethiopia from June to September 2013. A total of 532 healthcare workers involved in the study. Data were collected by using a pre-tested and structured interview questionnaire. Data were analyzed using SPSS for windows version 16.0. Multivariable analyses were employed to see the effect of explanatory variables on dependent variable. A total of 276(51.9%) healthcare workers experienced occupational exposure to HIV infection within the last one year. Recapping of needles [AOR: 3.1, 95%CI: (2.1, 4.6)], lack of training on infection prevention and patient safety [AOR: 3.3, 95%CI: (1.6, 5.8)], and night workshift [AOR: 3.4, 95%CI: (1.1, 6.9)] were found to be the independent predictors of occupational exposure to HIV infection.This study revealed that the prevalence of occupational exposure to HIV infection among HCWs in government health institutions was high. So, effective HIV prevention measures should target on areas, such as proper design and use of needles, provision of adequate training on infection prevention and patient safety, and monitoring of shiftwork schedules.Keywords: Healthcare workers, HIV infection, Occupational exposure.